Transnational Networks and Social Cohesion Among Climate-Displaced Populations: A Cross-Sectional Study in Coastal Indonesia - Immanuel Simbolon; Desiree Montesinos; Jujuk Maryati (HM Publisher, 2026)
Climate-induced displacement in coastal Indonesia creates unprecedented challenges for affected populations seeking economic stability and psychological resilience. This cross-sectional analytical study examined the role of transnational networks, social cohesion, government support, and digital connectivity in climate adaptation success among 373 internally displaced persons (IDPs) across three coastal districts (Demak, Pekalongan, and Indramayu) in Central Java from January to June 2024. Using binary logistic regression, we assessed nine predictors of successful climate adaptation, defined as sustainable livelihood restoration and psychological well-being. Transnational Network Strength (TNS) emerged as the strongest predictor (adjusted odds ratio [AOR] = 2.58, 95% CI 1.59–4.18, p < 0.001), followed by Social Cohesion (AOR = 2.14, 95% CI 1.33–3.44, p = 0.002) and Government Support (AOR = 1.62, 95% CI 1.03–2.56, p = 0.038). Digital Connectivity Index and low psychological distress were also significant protective factors (AOR = 1.68, p = 0.034 and AOR = 1.82, p = 0.014, respectively). The multivariate model demonstrated good discrimination (area under the curve = 0.81) and acceptable calibration (Hosmer-Lemeshow p = 0.592), with 75.3% overall accuracy. Partial correlation analysis revealed a moderate positive association between TNS and social cohesion (r = 0.47, controlling for confounders). These findings underscore the critical importance of fostering transnational connections, strengthening community bonds, and expanding digital access to enhance adaptation outcomes among climate-displaced populations in vulnerable coastal regions.